Օսմանյան կայսրությունում ցեղասպանության քաղաքականության ակունքների հարցի շուրջ, հակազդեցություն 1876թ. բուլղարական ապստամբությանը - Ռուբեն Սաֆրաստյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
В статье впервые рассматривается реакция турецких властей на Болгарское восстание 1876г. с точки зрения геноцидологии. Автор приходит к мнению, что реакция является переходным этапом от "традиционной" политики погромов Османской империи до политики геноцида. In the paper for the first time the responce of Turkish authorities to the Bulgarian Upprising of 1876 is beeng reviewed from the stand point of the Genocidology. Author draws conclusion that the responce constitued a transitional Stage from "traditional" for the Ottoman Turkey police of massacres towards to the genocide policy.
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)